Genetic Diversity Analysis and Determination of Specific Alleles of Kuantan Cattle Using Microsatellite Markers - R. Misrianti; S. H. Wijaya; C. Sumantri; J. Jakaria (Faculty of Animal Science, Bogor Agricultural University, 2022)
Kuantan cattle have an important role in Riau Province, Indonesia. Identification of the genetic diversity of these cattle is important to get the basic information for breeding and conservation strategies. The aim of this research was to identify the genetic diversity of Kuantan cattle using microsatellite markers. A total of thirty-nine DNA samples from three breeds were used in this study. The polymerase chain reaction was conducted using four labeled primers of microsatellite (INRA035, ILSTS06, HEL9 and ETH225). The data were analyzed using GenAlEx 6.41, Cervus 3.0, POPTREE, and STRUCTURE Software. A total of thirty-two alleles were found from microsatellite loci. Two alleles in INRA035 locus 112 and 118 occurred as specific allele candidates for Kuantan cattle. The mean of observed heterozygosity value of the Kuantan-2 population (0.602) was higher than Kuantan-1 (0.471) but lower than Madura (0.688) and Pesisir cattle (0.625). PIC value was higher in HEL9 loci. The dendrogram showed that Kuantan cattle existed at different clusters with Pesisir and Madura cattle. This finding indicated that microsatellite markers successfully distinguished clusters of the cattle and could serve as information for conducting conservation and breeding program.